The State of Education in Ukraine and the Role of Education Managers in Problem-Solving (Global Journal of Management and Business Research, 2023)
For an educational system, or any system for that matter, the terms which lift the weight are management and leadership. By the dawn of the past century, much attention has been given to these two terms for their magnitude of importance and implication. When it comes to the educational facility and the question of allocating the available resources to achieve the maximum goals, it becomes crystal clear that a figure with influence is needed in the educational playground, so to speak. This review shed some light on these points and illustrates their use.
Keywords: ukraine; strategy; leader; school management; places of conflict